O realismo do romance contemporâneo de Bernardo de Carvalho: uma narrativa labiríntica em abismo - Lemos, Sandra Maria Fontinha de (2014)
This academic research clings to the analysis of the novel O Sol Se Põe Em São Paulo, by Bernardo Carvalho as a representative sample of the Brazilian contemporary novel. In this paper we intend to show the features that define the different phases of the genre and the features which are still being used in the contemporary novel. For that we tried to understand the architectural-narrative of the corpus s text, decode what kind of conundrum the novel deals with and what kind of issues have the characters faced. All these issues are previously established as a basis to a hypothesis namely, the echogenic analysis of the text. We studied the process of the text production taking into consideration the wiles used by Bernardo Carvalho and that he took as stratagem to echo reflection, as an art craft amplifier. We acknowledge that these art crafts work as a mirrored system repeating the same function. Another subject analyzed in this paper is the role and the function of the voices, its interaction. We tried to pinpoint the fact that all the wiles used by the author follow the same stratagem, the same objective and that although these wiles had being used before, separately, they represent the idea that contemporary literature speaks of: that is an egotic literature. To sustain the critical-theorical foundation upon which this thesis is structured we chose some authors: Mikhail Bakhtin, Clement Rosset, Otto Rank, Lucien Dallenbach, Tzvetan Todorov, Michel de Certeau, and Merleau Ponty, among others. Along these three chapters we developed a cohesive text in which we could put up with the proposed theories and themes in accordance with the Bernardo Carvalho`s novel we analized. It stood out how the duplication, the mise en abyme and the exotopy reverberate, by the voice and the word, throughout the text drawing a realistic image in this contemporary novel